The Fairly OddParents. Wishology! [videorecording (DVD)] (Viacom International, Inc., 2011)
"First there was The lord of the rings. Then came Star wars. The world's wish for another epic masterpiece has finally come to pass with the Fairly OddParents trilogy 'Wishology!' It's the three-part tale of how a hero--prophesized to don a pink hat and have buckteeth, and whose initials are 'T.T.'--must take on a bunch of evil robots and the ultimate evil: the darkness. Guest starring the likes of Gene Simmons and Paul Stanley of KISS, Patrick Warburton, and Brendan Fraser, this legend will keep you glued to your seat, as Timmy Turner must firgure out how to save the world--without the help of his fairy godparents!"--Container.